2019
DOI: 10.1038/s41523-018-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

MONARCH 3 final PFS: a randomized study of abemaciclib as initial therapy for advanced breast cancer

Abstract: At the MONARCH 3 interim analysis, abemaciclib plus a nonsteroidal aromatase inhibitor (AI) significantly improved progression-free survival (PFS) and objective response rate (ORR) with a tolerable safety profile as initial treatment for hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) advanced breast cancer (ABC). MONARCH 3 is a randomized, phase III, double-blind study of abemaciclib/placebo (150 mg twice daily, continuous) plus nonsteroidal AI (1 mg anastrozole or 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
417
1
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 467 publications
(464 citation statements)
references
References 28 publications
25
417
1
21
Order By: Relevance
“…The patients were randomized 2:1 to receive abemaciclib with anastrozole or letrozole compared to placebo plus anastrozole or letrozole. The results showed that the abemaciclib arm had better median PFS than the placebo arm (28.18 versus 14.76 months) [149], which also led to the FDA approving abemaciclib (Verzenio) in combination with aromatase therapy in HR+/HER2− M/ABC patients as first-line therapy in February 2018. In addition, other ongoing studies with abemaciclib in BC were carried out, such as the neoMONARCH (NCT02441946) phase II clinical trial to compare the biological effects of abemaciclib combination with anastrozole to those of abemaciclib monotherapy and anastrozole monotherapy for two weeks, as well as to evaluate the activity and safety of abemaciclib with anastrozole in a subsequent 14 weeks with HR+/HER2− ABC [150].…”
Section: The Clinical Success Of Cdk4/6-selective Inhibitors In Bcmentioning
confidence: 99%
“…The patients were randomized 2:1 to receive abemaciclib with anastrozole or letrozole compared to placebo plus anastrozole or letrozole. The results showed that the abemaciclib arm had better median PFS than the placebo arm (28.18 versus 14.76 months) [149], which also led to the FDA approving abemaciclib (Verzenio) in combination with aromatase therapy in HR+/HER2− M/ABC patients as first-line therapy in February 2018. In addition, other ongoing studies with abemaciclib in BC were carried out, such as the neoMONARCH (NCT02441946) phase II clinical trial to compare the biological effects of abemaciclib combination with anastrozole to those of abemaciclib monotherapy and anastrozole monotherapy for two weeks, as well as to evaluate the activity and safety of abemaciclib with anastrozole in a subsequent 14 weeks with HR+/HER2− ABC [150].…”
Section: The Clinical Success Of Cdk4/6-selective Inhibitors In Bcmentioning
confidence: 99%
“…Three CDK 4/6 inhibitors (palbociclib, ribociclib, and abemaciclib) are used in the treatment of metastatic HR+, HER2 negative BC. CDK 4/6 inhibitors are indicated only in combination with endocrine therapy (AI or fulvestrant) [64][65][66][67]. Laezza et al showed that anandamide analogue (Met-F-AEA) induces S-phase cell cycle arrest and decreases the percentage of cells in G2/M phase in the MDA-MB-231 line.…”
Section: Inhibitors Of Cyclin Dependent Kinasesmentioning
confidence: 99%
“…Inhibition of CDK4/6 with a small molecule prevents cell-cycle progression through G 1 and arrests tumor growth. Abemaciclib is one of three currently approved selective small-molecule inhibitor of CDK4/6 for treatment of HR þ /HER2 À metastatic breast cancer, the other two being palbociclib and ribociclib (8)(9)(10)(11)(12)(13)(14). In preclinical studies, short-term inhibition caused temporary G 1 arrest in vitro and in vivo (9,13).…”
Section: Introductionmentioning
confidence: 99%